2008
DOI: 10.2337/db07-1305
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Susceptibility Locus for Type 1 Diabetes on Chr12q13 Identified by a Genome-Wide Association Study

Abstract: OBJECTIVE—In stage 1 of our genome-wide association (GWA) study for type 1 diabetes, one locus at 16p13 was detected (P = 1.03 × 10−10) and confirmed in two additional cohorts. Here we describe the results of testing, in these additional cohorts, 23 loci that were next in rank of statistical significance. RESEARCH DESIGN AND METHODS—Two independent cohorts were studied. The Type 1 Diabetes Genetics Consortium replication cohort consisted of 549 families with at least one child diagnosed with dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 21 publications
4
95
2
1
Order By: Relevance
“…This attenuated TCR/CD3 signaling could synergize with the 50% reduction in IL-2 abundance and correlate with the reduced function of regulatory T cells reported to be conferred by the NOD allele of the Idd3 locus (49). As recently discussed (50), such a scenario concurs with the quantal theory of immunity, stating that T cell responses depend on cells receiving a critical number of TCR-and IL-2R-mediated stimuli, which, in turn, may have consequences for the process of discrimination between self and nonself (51). The results are also consistent with recently published observations that haplotypes in the human IL2RA gene associated with human T1D and multiple sclerosis correlate with differences in the surface expression of IL-2Ra (50).…”
Section: Discussionsupporting
confidence: 58%
“…This attenuated TCR/CD3 signaling could synergize with the 50% reduction in IL-2 abundance and correlate with the reduced function of regulatory T cells reported to be conferred by the NOD allele of the Idd3 locus (49). As recently discussed (50), such a scenario concurs with the quantal theory of immunity, stating that T cell responses depend on cells receiving a critical number of TCR-and IL-2R-mediated stimuli, which, in turn, may have consequences for the process of discrimination between self and nonself (51). The results are also consistent with recently published observations that haplotypes in the human IL2RA gene associated with human T1D and multiple sclerosis correlate with differences in the surface expression of IL-2Ra (50).…”
Section: Discussionsupporting
confidence: 58%
“…Autoantibody measurements were not available in the present study, but we have recently shown that rs2292239 is associated with multiple autoantibodies in longstanding T1D (Brorsson and Pociot, 2015). We could not replicate the finding that rs2292239 was associated with a lower age at onset (Hakonarson et al, 2008;Espino-Paisan et al, 2011), most likely due to the fact that all children in our cohort were diagnosed before the age of 11 years.…”
Section: Discussioncontrasting
confidence: 66%
“…Originally, association with T1D was demonstrated for the single nucleotide polymorphism (SNP) rs11171739, which maps between the RPS26 and ERBB3 genes (Burton et al, 2007). Most studies, including a meta-analysis, identified the strongest association with the single nucleotide polymorphism (SNP) rs2292239, located in intron 7 of ERBB3 (Barrett et al, 2009;Onengut-Gumuscu et al, 2015;Burton et al, 2007;Hakonarson et al, 2008;Todd et al, 2007;Keene et al, 2012). Genetic variations in ERBB3 have also been used in different model approaches to improve prediction of T1D (Winkler et al, 2012;Bonifacio et al, 2014), autoimmunity (T€ orn et al, 2015;Brorsson and Pociot, 2015) and disease progression (Achenbach et al, 2013;Andersen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The genotypes associated with T1D produce lower ERBB3 mRNA expression and reduced ERBB3 expression on TLRactivated dendritic cells and monocytes and a lower ability to stimulate T cell proliferation [103]. This locus was subsequently independently identified in the T1DGC and Canadian replication cohorts by Hakonarson et al (2008) [104].…”
Section: Erbb3mentioning
confidence: 99%